Mortality rates due to Bladder cancer in Iran during 2001-2007: A national cancer registry-based study - Khayamzadeh, Maryam; Aliakbari, Fereshte; Zolghadr, Zahra; Emadeddin, Majid; Moradi, Afshin; Akbari, Mohammad Esmaeil; Abedi, Amir Reza; Nematollahi, Shahrzad; Hosseini, Jalil (Archives of Men's Health, 2019)
Introduction: Bladder cancer is the ninth common cause of cancers in both sexes worldwide. Nevertheless, little is known about the descriptive and analytic epidemiology of bladder cancer in Iran. The present study aimed to describe the nationwide distribution of death due to bladder cancer in Iran. Methods: This cross-sectional study used data of bladder cancer cases who were registered in the national cancer-registry system by the Ministry of Health and Medical Education during 2001-2007. Age-standardized mortality rates due to bladder cancer were presented according to nine geographic poles across the country. Results: The overall mortality rate of bladder cancer (per 100,000 population) was 2.26 in men and 1.36 in women; while the rates were constantly higher for men across all age groups. The highest and lowest age-standardized mortality rates in provinces (per 100,000 population) belonged to Mazandaran (6.126) and Tehran (1.112), respectively. Conclusion: Death from bladder cancer seems to increase by age in Iran, mainly among men. This association might be partially due to increased life expectancy, altered high-risk lifestyle behaviors and/or improvement in cancer registration system. Information on the distribution of mortality due to bladder cancer could be useful for local prevention strategies, where specific profile of communities and patients is taken into account.